Characterization Of Oil-In-Water Emulsions: An Evaluation Of The Coulter Counter Technique - H. A. Hamza; N. E. Andersen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1980)
Emulsions have long occupied an important position in many industries. In the petroleum industry, where enhanced oil recovery techniques such as steam stimulation, flooding, etc. are being increasingly practiced, emulsions are very frequently produced. Characterization of these emulsions are an important prerequisite for monitoring and evaluation of the recovery processes. Emulsion properties will also determine the type of treatment required to separate and recover the oil phase. A variety of laboratory, pilot-scale and field-generated emulsions were characterized. Coulter technique results for size analysis are compared with microscopy (image analysis) and laser light scattering methods; Coulter determined oil contents are compared with gravimetric and volumetric methods of analysis.